John Fries’ Rebellion (1799–1800) - Daszyńska, Jolanta A. (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
Fries’ Rebellion of 1799 was an uprising, in opposition to a direct federal property tax. It was an armed tax revolt led by John Fries. In July 1798, the Federalist-controlled U.S. Congress, voted a direct tax on all real property, including buildings, land and slaves. This tax widespread the national resentment against the “Allien and Sedition Acts”, which infuriated the German farmers of Bucks, Northampton, and Montgomery counties in Pennsylvania. Several hundred farmers took up arms. At Bethlehem, Pa. Fries and his men forced a group of tax resisters who had been imprisoned under the custody of the federal marshal. In response, President Adams called out a force of federal troops of militia, who marched into the rebellious counties and began making wholesale arrests of the insurgents. John Fries was captured and subsequently tried twice, convicted of treason and sentenced to hang. He was pardoned by Adams who declared a general amnesty for all those who had been involved in the rebellion.